FRI0204 Comparison the long-term clinical outcomes between nontnf-inhibitors versus tnf-i in ra patients who failed to a first tnf-i. (15th June 2017) - Bogas, P; Plasencia, C; Pascual-Salcedo, D; Bonilla, G; Moral, E; Tornero, C; Nuño, L; Villalba, A; Peiteado, D; Martinez, A; Hernandez, B; Balsa, A
Abstract : Background: There are many biological therapies for Rheumatoid Arthritis (RA) with different mechanisms of action and good efficacy rate; however, up to 40% of patients (pts) fail to respond to the 1st biologic agent, and it is still not clear what strategy to follow after showing inadequate response to tumor necrosis factor α inhibitors (TNF-i) Objectives: To assess the clinical response and survival (SVV), in our cohort of RA pts that discontinued the 1st TNF-i, of a 2nd TNF-i vs a nonTNF-i, both in the global cohort and in the subpopulation that dropped out the 1st TNF-I due to inefficacy Methods: This observational study included 110 pts in the RA-Paz cohort who previously suspended Ifx (68%) or Ada (32%) between 1999–2016. Two groups were established as they switched to a TNF-i or nonTNF-i. Clinical response was evaluated by DAS28, Delta-DAS28 (ΔDAS28) and EULAR response (E-resp). The assessments were performed at 6 (v-6) and 12 months (v-12) since initiating 2nd biological agent and during the last visit prior to drug discontinuation or ending of the study for those who did not interrupt the drug (v-end). Statistical analysis was performed using SPSS version 20.0 Results: Of the 110 pts who had stopped Ifx or Ada as 1st TNF-i, 65% changed to a 2nd TNF-i. The 84% of the overall pts were women. The mean age was 64±14 years and the mean time of 2nd biologic drug was 3.71±3.51 years. 61% associated methotrexate at the beginning of 2nd biologic agent and 56% at the v-end, without differences between those who switched to TNF-i and those who did to nonTNF-i. At v-6 and v-12, there was no difference in ΔDAS28 [at v-6:1.3±1.4 in TNF-i and 1.2±1.2 in nonTNF-i (p=0.919), at v-12: 1.3±1.5 in TNF-I and 1.2±1.1 in nonTNF-i (p=0.852)]. In contrast, at v-end, pts with nonTNF-i showed a higher clinical improvement (ΔDAS28: 0.68±1.7 in TNF-i, 1.8±1.1 in nonTNF-i, p=0.002). At v-6, the TNF-i group achieved higher good E-resp rate (41% vs 18%, p=0.035), but there was no difference at v-12 (36% in TNF-I vs 23% in nonTNF-i, p=0.435). However, at v-end, the nonTNF-I group achieved better E-resp (good resp: 38% in nonTNF-i vs 25% in TNF-I, no resp 18% in nonTNF-i vs 50% in TNF-i, p=0.01). Likewise, 100% (n=7) of the pts that finished 2nd biologic agent by remission, had changed to a nonTNF-i (p<0.00001). There were no differences regarding 2nd biologic drug SVV (mean SVV time of 5.7±0.66 in TNF-I, 4.3±0.59 in nonTNF-i, p=0.797). When analyzing the cohort that discontinued 1st TNF-I because of inefficacy, at v-6 and v-12 there were no differences between switchers to TNF-I and nonTNF-i in ΔDAS28 [v-6: 1.4±1.4 vs 0.9±1 p=0.164); v-12: 1.5±1.4 vs 1±1, p=0.192)], but at v-end, the nonTNF-i group reached a higher ΔDAS28 (0.9±1.5 in TNF-i, 1.6±1 in nonTNF-i, p=0.031) Conclusions: In our sample of RA patients who suspended Ifx/Ada as 1st TNF-i, switching to a 2nd biologic agent did not show relevant clinical differences between a TNF-i and a nonTNF-i within the 1st year of treatment. However, in the long-term, switching to a nonTNF-i shows enhanced clinical benefits with no impact on survival vis-à-vis a 2nd TNF-i. Despite the efficacy of TNF-i, new therapeutic targets are needed for those who fail to respond to these biological agents Disclosure of Interest: None declared